Polyphasic characterization and mating type allele distribution of Monilinia laxa in Iranian stone fruit orchards - Hadi Golmohammadi; Mahdi Arzanlou; Hossein Jafary; Mounes Bakhshi (Scientific Reports)
Abstract Brown rot disease, caused by species of the genus Monilinia, is a significant fungal disease affecting pome and stone fruit trees. In this study, 565 samples were collected from symptomatic trees across six provinces of Iran between 2018 and 2022. A total of 430 fungal isolates were obtained and identified using both morphological and molecular techniques. PCR assays with species-specific primers revealed that 403 isolates belonged to Monilinia laxa and 27 to Monilinia fructigena. Sequencing of the ITS and Ef-1α gene regions was performed for 12 representative isolates, and Bayesian phylogenetic analysis confirmed species-level identification. Mating-type determination was carried out using newly designed primers targeting the Mat1-1-1 and Mat1-2-1 genes, successfully detecting both mating types in the two species. Pathogenicity tests on apricot, sour cherry, sweet cherry, and plum fruits demonstrated that all selected isolates were highly pathogenic, producing visible symptoms within 3 to 4 days post-inoculation, which led to complete fruit rot and mummification within 23 days. Morphological characterization showed that M. laxa colonies exhibited lobed margins and variable pigmentation, while M. fructigena had smooth colony margins with peach-colored centers. Conidia were blastic, aseptate, and formed in chains, with distinguishable size differences between species. This study provides comprehensive data on the distribution, genetic diversity, mating-type structure, and pathogenic potential of Monilinia spp. in Iran, offering valuable insights for disease monitoring and integrated management strategies in affected orchards.